Putting the Parts of the Whole Together: Systematic Arrangement of Archives - Eastwood, Terry (Archivaria, 2000)
This article aims to characterize the principled rules that can be used to develop a standard approach to arrangement of archives. It proposes a number of rules for identification of the various aggregations of records that form the externaland internal structure of a fonds. It also examines the differences between the approaches to arrangement of systems based on the concept of the fonds and on series control. It concludes that, contrary to a commonly held opinion, it is not our understanding of the terms of arrangement that impedes intellectual control of archives, but rather the difficulties in developing systems capable of communicating informationabout the complex of aggregations forming an archives and their relationships. RÉSUMÉ L’objectif de cet article est de déterminer les principes qui peuvent êtreutilisés afin de développer une approche standardisée pour servir au classement des documents d’archives. L’auteur y propose un certain nombre de règles pour identifierles différents regroupements de documents dont découlent les structures externe etinterne d’un fonds. Il examine également les différences entre les approches declassement basées sur le concept du fonds ou sur celui de la série. La conclusion de l’article est que, contrairement à l’idée couramment acceptée, ce n’est pas notre mauvaise compréhension de l’arrangement des documents qui entrave leur contrôle intellectuel, mais plutôt la difficulté de développer des systèmes capables de communiquer l’information au sujet de la complexité des regroupements de documents d’archives et de leurs relations entre eux.